Aspen Tension Wood Fibers Contain β-(1→4)-Galactans and Acidic Arabinogalactans Retained by Cellulose Microfibrils in Gelatinous Walls. Issue 3 (16th September 2015) - Gorshkova, Tatyana; Mokshina, Natalia; Chernova, Tatyana; Ibragimova, Nadezhda; Salnikov, Vadim; Mikshina, Polina; Tryfona, Theodora; Banasiak, Alicja; Immerzeel, Peter; Dupree, Paul; Mellerowicz, Ewa J.
Abstract : Entrapment of pectic galactan and acidic arabinogalactan II within cellulose fibrils is a distinctive feature of aspen tension wood gelatinous fibers with contractile properties. Abstract: Contractile cell walls are found in various plant organs and tissues such as tendrils, contractile roots, and tension wood. The tension-generating mechanism is not known but is thought to involve special cell wall architecture. We previously postulated that tension could result from the entrapment of certain matrix polymers within cellulose microfibrils. As reported here, this hypothesis was corroborated by sequential extraction and analysis of cell wall polymers that are retained by cellulose microfibrils in tension wood and normal wood of hybrid aspen ( Populus tremula × Populus tremuloides ). β-(1→4)-Galactan and type II arabinogalactan were the main large matrix polymers retained by cellulose microfibrils that were specifically found in tension wood. Xyloglucan was detected mostly in oligomeric form in the alkali-labile fraction and was enriched in tension wood. β-(1→4)-Galactan and rhamnogalacturonan I backbone epitopes were localized in the gelatinous cell wall layer. Type II arabinogalactans retained by cellulose microfibrils had a higher content of (methyl)glucuronic acid and galactose in tension wood than in normal wood. Thus, β-(1→4)-galactan and a specialized form of type II arabinogalactan are trapped by cellulose microfibrils specifically in tension wood and, thus, are the main candidate polymers for the generation of tensional stresses by the entrapment mechanism. We also found high β-galactosidase activity accompanying tension wood differentiation and propose a testable hypothesis that such activity might regulate galactan entrapment and, thus, mechanical properties of cell walls in tension wood.